Education for sustainable healthcare: opportunities and barriers in undergraduate health professions education in South Africa - Irlam, James (Department of Public Health and Family Medicine, 2025)
The escalating global crisis of climate change and environmental degradation is having severe public health impacts. One key response requires faculties of health sciences globally to review how they prepare their health professional graduates to address the changing needs of the communities they serve. Health professions education has generally not kept pace with changing societal needs, and current curricula are often too fragmented and static to prepare graduates as effective climate health leaders and agents of change. Education for sustainable healthcare (ESH) is a field in health professions education focused on the interdependence of human health and planetary ecosystems, and on making healthcare systems more environmentally sustainable. ESH incorporates the principles of planetary health, which recognises that informed stewardship of earth's natural systems is essential for human health and well-being. ESH also includes education about environmentally sustainable healthcare, which is high-quality healthcare that is less polluting and wasteful of natural resources than conventional healthcare. There is, however, little evidence about ESH from low- and middle-income countries, which are generally most impacted by climate and environmental breakdown. The aim of this thesis was to identify the opportunities and barriers to ESH in undergraduate health professions education in South Africa, illustrated by a case study at the University of Cape Town Faculty of Health Sciences (UCT FHS). A mixed methods study of three sequential phases addressed four objectives. Phase 1 was a national survey of key educators to assess the status of ESH-related teaching and learning activities in undergraduate health professions education in South Africa. Phase 2 recruited a national Delphi panel of educators for the second objective of appraising the ESH learning objectives, activities, and assessments proposed by the International Association for Health Professions Education (AMEE) Consensus in 2021. The Delphi panel also helped achieve the third objective, to assess perceptions of educators about the opportunities and barriers to ESH in South Africa. The third phase was a Planetary Health Report Card (PHRC) assessment of the UCT FHS, by interviewing key educators and completing standardised scorecards. This phase addressed the fourth objective, to assess perceptions of educators about the opportunities and barriers to ESH in the UCT FHS. The thesis is structured into seven chapters. Chapter 1 provides the rationale, aim, objectives, design, and structure of the thesis. Chapter 2 reviews the literature on the health impacts of climate change, and the contribution of ESH towards social and environmental accountability in health professions education. It presents the conceptual framework of the thesis for evaluating environmental accountability in health professions education institutions, derived from the Conceptualisation, Production, and Usability (CPU) model for socially accountable medical schools. Chapter 3 describes the national audit survey in Phase 1, which found that ESH curriculum development is emerging in South Africa and is enabled by strong institutional leadership and by staff and student involvement. Chapter 4 analyses the findings of the national Delphi panel in Phase 2. It reached consensus on a set of learning objectives, activities, and assessments for health professions education in South Africa and identified enablers of ESH curricular development, among them faculty leaders, capable educators, and multidisciplinary collaboration. Chapter 5 presents the baseline findings of the PHRC assessment of the curricula, research, community engagement, student leadership, and campus sustainability of the UCT FHS. The PHRC identified curriculum overload, “siloed” learning, limited educator capacity, and health system challenges as key barriers, and recommended longitudinal integration of ESH across all curricula. Chapter 6 presents the discussion of the overall findings of the study. It proposes a framework for guiding ESH curricular development, which integrates recommendations in six focus areas for faculty leaders and educators within three domains of the CPU model. The key barriers and enablers of ESH identified by this study, and examples of opportunities in the UCT FHS, are also discussed. Chapter 7 concludes with the contribution of the study to knowledge about ESH and the implications for future research. The thesis has helped to build the evidence about ESH from a LMIC perspective. It has identified barriers and opportunities within South African undergraduate health professions education, and has proposed learning objectives, activities, and assessments for the South African context. A PHRC assessed opportunities for ESH integration in the UCT FHS, a first in the global South. The thesis proposes an integrated ESH curricular development framework within a social accountability model for HPE institutions, with potential applicability to low- and middle-income countries.